2020
DOI: 10.33271/mining14.04.113
|View full text |Cite
|
Sign up to set email alerts
|

Review of unconventional hydrocarbon resources: production technologies and opportunities for development

Abstract: Purpose. Study the state of modern technologies for the extraction of unconventional hydrocarbon resources and determine the prospects for their development. Methods. The method of qualitative and quantitative analysis of scientific literature, data from the U.S. Energy Information Administration, national reports on the Extractive Industries Transparency Initiative standard, as well as open Internet sources, are used in the research. Structurally, the research consists of a sequential analysis of the main typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Weight-based methods often assume that reservoir properties, such as porosity and saturation, are uniform throughout. In reality, reservoirs may exhibit significant heterogeneity, which may affect the assessment of reserves (Tolmachev et al 2020;Panikarovskiy et al 2021). In our study, we confirmed these conclusions by measuring the porosity of core samples of the Cenomanian deposits using MCT and liquid saturation methods.…”
Section: Discussionsupporting
confidence: 82%
“…Weight-based methods often assume that reservoir properties, such as porosity and saturation, are uniform throughout. In reality, reservoirs may exhibit significant heterogeneity, which may affect the assessment of reserves (Tolmachev et al 2020;Panikarovskiy et al 2021). In our study, we confirmed these conclusions by measuring the porosity of core samples of the Cenomanian deposits using MCT and liquid saturation methods.…”
Section: Discussionsupporting
confidence: 82%
“…Energies 2022, 15, 3491 2 of 25 constitute a vital and sustainable solution to safely capture and permanently store CO 2 and other greenhouse gas emissions (GHG), for which permeable geologic formations are already being considered environmentally safe and economically viable solutions [5,6]. Moreover, throughout lab and field experiments, the potential of CO 2 use for geological carbon storage (GCS) and enhanced oil/gas recovery in shales, as well as the partial replacement of CH 4 with CO 2 , has been confirmed [7][8][9]. In recent years, research has been conducted focusing on determining the most appropriate geological formations as natural reservoirs for CO 2 , either for utilization or long-term storage via sequestration, with the formation of new stable mineral phases.…”
Section: Introductionmentioning
confidence: 94%
“…Russia ranks second in the world in terms of coal reserves. According to various estimates, 17.6 to 18.2% of these mineral reserves are concentrated in Russia (over 157 billion tons) (Tolmachev et al, 2020). According to OPEC, oil reserves (at current production volumes) will last for 30-40 years, natural gas for 75-80 years, and coal for 400-500 years (Goncharenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%